Strategies for Ensuring Customers’ Satisfaction by Business Entrepreneurs for Sustainability of Livelihood in Oyo State - Ayinde Dauda Oladeji; Popoola Balqis Olabisi; Muraina Kamilu Olanrewaju (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Customer satisfaction is one of the essential things that must be maintained. This research aims to analyze the various strategies that entrepreneurs can use to build customer satisfaction for sustainable livelihoods. This study used a descriptive survey design. The study population consisted of 3,659 managers of small and medium-sized enterprises registered with the Ministry of Commerce, Industry, and Technology. The sample of this study amounted to 783 small and medium-sized business owners who were taken through a proportional stratified sampling technique. The data collection instrument in this study was a structured questionnaire titled "Questionnaire on Building Customer Satisfaction Strategies for Sustainable Livelihoods" (SBCSSL). The face validity of the instrument was determined using expert opinions. The reliability of the instrument was calculated using Cronbach Alpha. Arithmetic mean and standard deviation were used to answer the research questions, while an independent sample t-test was used to test the hypotheses. The findings revealed, among others, that business entrepreneurs essentially rated employee empowerment, entrepreneurial orientation, and marketing as strategic to building customer satisfaction for sustainable livelihood. Based on the research findings, it is recommended, among others, that business owners should be open and eager to implement entrepreneurial innovations at a higher level to enhance their growth and competitiveness, profitability, and survival.